Association between braf gene mutation status and clinical-morphological features of cutaneous melanoma - O. I. Kit; D. I. Vodolazhsky; E. Yu. Zlatnik; I. Yu. Efimova; S. S. Kochuev; Yu. V. Przhdetsky (Кубанский научный медицинский вестник, 2016)
This study identified associations between mutation status of the BRAF gene and the clinico-morphological features of melanoma patients in the South of Russia of the age group over 55 years. It was carried out molecular genetic study of exon 15 of the BRAF gene sequencing method of Sanger and by RT-PCR in 35 patients in Southern Russia with morphologically confirmed diagnosis of skin melanoma. The study found that the presence of mutations in the gene BRAF was significantly associated with increasing tumor thickness according to Breslow. We also observed an increase in the frequency of ulceration of the tumor by 21% in patients with an activating V600 mutation. The frequency of detection of V600 mutations in the BRAF gene in tissues of melanoma was 40%.